Ultrafast-charging and long cycle-life anode materials of TiO2-bronze/nitrogen-doped graphene nanocomposites for high-performance lithium-ion batteries. Issue 71 (8th December 2020) - Autthawong, Thanapat; Chimupala, Yothin; Haruta, Mitsutaka; Kurata, Hiroki; Kiyomura, Tsutomu; Yu, Ai-shui; Chairuangsri, Torranin; Sarakonsri, Thapanee
Abstract : The TiO2 -bronze/nitrogen-doped graphene nanocomposites have the potential for fast-charging and have high stability, showing potential as an anode material in advanced power batteries for next-generation applications. Abstract : Emerging technologies demand a new generation of lithium-ion batteries that are high in power density, fast-charging, safe to use, and have long cycle lives. This work reports charging rates and specific capacities of TiO2 (B)/N-doped graphene (TNG) composites. The TNG composites were prepared by the hydrothermal method in various reaction times (3, 6, 9, 12, and 24 h), while the N-doped graphene was synthesized using the modified Hummer's method followed by a heat-treatment process. The different morphologies of TiO2 dispersed on the N-doped graphene sheet were confirmed as anatase-nanoparticles (3, 6 h), TiO2 (B)-nanotubes (9 h), and TiO2 (B)-nanorods (12, 24 h) by XRD, TEM, and EELS. In electrochemical studies, the best battery performance was obtained with the nanorods TiO2 (B)/N-doped graphene (TNG-24h) electrode, with a relatively high specific capacity of 500 mA h g −1 at 1C (539.5 mA g −1 ). In long-term cycling, excellent stability was observed. The capacity retention of 150 mA h g −1 was observed after 7000 cycles, at an ultrahigh current of 50C (27.0 A g −1 ). The synthesized composites have the potential for fast-charging and have high stability, showing potential as an anode material in advanced power batteries for next-generation applications.